CRITICAL ANALYSIS OF THE IMPLEMENTATION OF ISLAMIC EDUCATION SUPERVISION - Sri Maeni; Suwuh Sopiyah; Teguh Santoso; Siswoyo; Titik Ulya (STKIP Subang, 2025)
Supervision of Islamic education plays a strategic role in improving the quality oflearning amidst the changing paradigm of national education, particularly throughthe Independent Curriculum. This study aims to analyze the implementation ofIslamic education supervision in Islamic educational institutions in Reban District,Batang Regency, and to identify its forms, challenges, and relevance to theIndependent Curriculum. This research uses a qualitative approach with a casestudy method in several madrasahs in Indonesia. Data collection techniquesinclude observation, in-depth interviews, and documentation. The results showthat supervision implementation encompasses academic, administrative, andspiritual dimensions. The main challenges stem from limited supervisorcompetency, resistance to organizational culture, and regulatory inconsistencies.However, supervision also has significant potential to become a lever for learningtransformation if conducted collaboratively and contextually. This studyrecommends strengthening supervisor capacity, integrating Islamic values intotraining, and updating supervision policies based on the Independent Curriculum.